2005
DOI: 10.1089/rej.2005.8.18
|View full text |Cite
|
Sign up to set email alerts
|

Stable Transformation of CHO Cells and Human NARP Cybrids Confers Oligomycin Resistance (olir) Following Transfer of a Mitochondrial DNA–Encoded olirATPase6 Gene to the Nuclear Genome: A Model System for mtDNA Gene Therapy

Abstract: Point and deletion mutations and a general depletion of mammalian mitochondrial DNA (mtDNA) give rise to a wide variety of medical syndromes that are refractory to treatment, possibly including aging itself. While gene therapy directed at correcting such deficits in the mitochondrial genome may offer some therapeutic benefits, there are inherent problems associated with a direct approach. These problems are primarily due to the high mitochondrial genome copy number in each cell and the mitochondrial genome bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 37 publications
0
25
0
1
Order By: Relevance
“…This chimeric protein eventually replaced the defective ATPase6 component in the complex. Later Manfredi et al and Zullo et al separately showed that ATPase6 subunit can be expressed in cytosol and be brought to mitochondria [78,79]. More work will have to be done to determine how general were these findings.…”
Section: Factors To Be Considered When Trying To Replace a Damaged Prmentioning
confidence: 99%
“…This chimeric protein eventually replaced the defective ATPase6 component in the complex. Later Manfredi et al and Zullo et al separately showed that ATPase6 subunit can be expressed in cytosol and be brought to mitochondria [78,79]. More work will have to be done to determine how general were these findings.…”
Section: Factors To Be Considered When Trying To Replace a Damaged Prmentioning
confidence: 99%
“…Possibly because of their high hydrophobicity, to date only four mitochondrial genes have been corrected in this manner, in plants (94) and yeast (99) and in cell culture (43,85,140). This approach is limited by the general difficulties of nuclear gene therapy, as well as problems with aggregation of some of the allotopic proteins (85).…”
Section: Mitochondrial Membranes and Dna Transfectionmentioning
confidence: 99%
“…Such reservations have been voiced by very senior figures in the field, (59,60) possibly contributing to the lack of manpower that has hitherto been applied to developing allotopic expression in mammals. The obstacles to functional allotopic expression are anyway highly challenging-modulating these proteins' hydrophobicity without impairing function will require much experimentation-but evolution does not, after all, appear to be telling us that recent progress in this area (61)(62)(63)(64) is a false dawn. The biomedical potential of successful, comprehensive allotopic expression is considerable: it would provide a cure for many presently incurable diseases caused by mtDNA mutations.…”
Section: The Hydrophobicity Hypothesis (Hh)mentioning
confidence: 99%